Tiger woman - Bandopadhyay, Sirsho; Sinha, Arunava (tr.) (New Delhi Picador, 2019)
Tiger Woman Calcutta, 1880s. Nationalism is on the rise and the Bengali intellectuals are leading the protest against British rule in India. In this charged climate, ardent patriot Priyanath Bose prepares to set up the first Bengali circus. Soon he discovers an exceptional young girl, Sushila, and trains her to be a trapeze artist. As the circus flourishes and big animal acts are introduced, Sushila and the tigers become the star attractions. But the prize Sushila craves is unattainable, as Priyanath, a married man, is forced to reject her love for him. Jilted, she begins a relationship with a fellow circus artiste
Keywords: English Fiction; Translated by Arunava SInha